(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article describes in detail the informative function of proto-philosophical forms of ideology, since ideas involving social relations and structure are compatible with other elements of social consciousness. After all, historical and philosophical analysis of the content of pre-scientific forms of ideology is becoming increasingly relevant. Ideology is a real spiritual process that grows and develops at the abstract theoretical level of thinking and as one of the components of social consciousness, its main function is the means and power of determining the direction of the future development of the country, including all current political processes. movement and strength.